Effects of Different Cropping Patterns on Maize (Zea mays L.) Yield - Yukui, Rui; Fafu, Rui; Jing, Hao (Comunicata Scientiae, 2011)
<span style="font-size: 12pt; background: white; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 宋体; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">Increasing maize yield per unit is the most important measure to address food security issues. Farmers from northeastern China created several cropping patterns to increase maize yield per unit, but which pattern is the best has not been researched systemically. A randomized block design of six cropping patterns and four replicates was used. Six cropping patterns 65cm×65 cm, 40cm×90 cm, 30cm×100 cm, 20cm×110 cm, 2L:0 and 4L:0 respectively were studied. The results showed that all wide and narrow rows patterns and free-sow patterns have higher yield than same spacing patterns, and 30cm×100cm is the optimal pattern to obtain the highest yield followed by 20cm×110cm, 4L:0, 2L:0, 40cm×90cm and 65cm×65cm respectively. According to our survey, more than four-fifths is the same spacing pattern (65cm×65cm) whose yield was 1.5t·ha-1 lower than wide and narrow rows with 30cm×100cm, so if all farmers carried out the 30cm×100cm pattern, food security of China <span style="font-size: 12pt; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 宋体; mso-font-kerning: 1.0pt; mso-ansi-language: EN; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN">problems will be obviously improved<span style="font-size: 12pt; background: white; color: black; font-family: "Times New Roman"; mso-fareast-font-family: 宋体; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-US">.